Os significados do propósito na carreira contemporânea - Farjo, Raissa Castilho (2019)
The present work aims to understand matters that permeate the social and economic relations, that refer to the work and values which are deepened in the political and cultural structure, bringing work closer to career and, especially, the purpose investigation, a widely disclosed and widespread term in the media and organizations, but still fragile regarding its definition, concept and academic production.The literature about the theme, mainly in the purpose field, it is still incipient, being most of the articles published by magazines and companies that exposes a concept that is still under construction. To trace the path of this search, we aim on reflecting from leaders of a corporative educational company, located in São Paulo, the interdisciplinary investigation of the concept of purpose and its meaning to the present-day career. For that, a case study research was made, considering the desire to comprehend the process of career from a new model of work that meets the need of an individual career purpose, a complex social and contemporary phenomenon.To be part of the research, we invited all the managing partners of the company (five), that have a leadership role, considering the CNS/MS 466/2012 Resolution, complemented by the CNS/MS 510/2016 Resolution, after approval at the Ethical Committee opinion nº 3.063.547. As methodology to acquire information, it was chosen the use of an adaptation of Dialogue Interview, systematized by Otto Scharmer (2015a), that opened the possibility to explore the individual career purpose of each participant, its relation to the work environment and its influence on the sense of working. By that, the present work pursues to contribute to this new field of study, developing a research in Psychology that considers the relationship between individual and its context, that from the data found on the case, exposes an opportunity to the definition of the purpose concept